2015
DOI: 10.1038/pr.2015.144
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biomarkers for systemic juvenile idiopathic arthritis

Abstract: Background: Differentiation of systemic juvenile idiopathic arthritis (SJIA) fever from other childhood fevers is often delayed due to the lack of reliable, specific biomarkers. We hypothesized that PD-L1 expression is dysregulated in SJIA monocytes and compared it to other candidate SJIA biomarkers. Methods: This pilot study enrolled children with fever without source and compared PD-L1 expression on myeloid cells to C-reactive protein, erythrocyte sedimentation rate, leukocyte counts, S100A12, S100A8, S100A9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 38 publications
1
10
0
1
Order By: Relevance
“…In patients with sJIA the median calprotectin level was 13,800 ng/ml, while in patients with the non-systemic disease type it was 2,700 ng/ml. Similar results were obtained in the study by Shenoi et al (2014), where the median level of calprotectin in patients with systemic-onset JIA was 38,600 ng/ml, and in patients with a non-systemic disease course it was 4,700 ng/ml [11]. …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In patients with sJIA the median calprotectin level was 13,800 ng/ml, while in patients with the non-systemic disease type it was 2,700 ng/ml. Similar results were obtained in the study by Shenoi et al (2014), where the median level of calprotectin in patients with systemic-onset JIA was 38,600 ng/ml, and in patients with a non-systemic disease course it was 4,700 ng/ml [11]. …”
Section: Discussionsupporting
confidence: 88%
“…The higher levels of calprotectin in patients involved in the Stanford University study can be explained by the fact that the majority of patients with sJIA had newly diagnosed disease [11]. In the study conducted at our clinic the highest calprotectin level was found in children with newly diagnosed sJIA (median 32,500 ng/ml, range: 13,800–177,000 ng/ml) (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…The search for more reliable biomarkers for seronegative arthritis has resulted in several serum proteins that are associated with disease activity in patients with seronegative arthritis: IL-6, IL-17, IL-23, VEGF, and MMP3 in SpA [6, 7, 4043], and IL-6 and IL-18 in JIA [5, 36, 44], amongst others. Although these proteins correlate with certain clinical aspects of seronegative arthritis, a major problem remains the lack of specificity, and results are often inconsistent; moreover, these putative biomarkers still await validation in cohort studies.…”
Section: Discussionmentioning
confidence: 99%
“…У хворих на сЮІА медіана рівня кальпротектину становила 13 800 нг/мл, а у пацієнтів із не-системним перебігом -2700 нг/мл. Подібні результати отримані у дослідженні Susan Shenoi (2014), де медіана кальпротектину у хворих на системний ЮІА становила 38 600 мкг/мл, а у пацієнтів із несистемним перебігом -4700 нг/мл [10]. Вищі рівні кальпротектину у хворих, залучених у дослідження Стенфордського університету, пояснюються тим, що у більшості хворих на сЮІА захворювання було діагностовано вперше.…”
Section: îáãîâîðåííÿunclassified